2013
DOI: 10.1111/echo.12455
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity Properties of Pulmonary Artery in Patients with Bicuspid Aortic Valve

Abstract: We demonstrated that elastic properties of pulmonary artery tend to be impaired as in the aorta in patients with BAV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…For flow to remain constant in a stiff pulmonary artery, the velocity and maximal frequency shift increase. It is reported that the formula (maximal frequency shift/acceleration time) indicated elastic properties of arteries (aorta or pulmonary artery) . PAS has been reported to be increased in subjects with bicuspid aortic valve, mitral stenosis, and systemic lupus erythematosus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For flow to remain constant in a stiff pulmonary artery, the velocity and maximal frequency shift increase. It is reported that the formula (maximal frequency shift/acceleration time) indicated elastic properties of arteries (aorta or pulmonary artery) . PAS has been reported to be increased in subjects with bicuspid aortic valve, mitral stenosis, and systemic lupus erythematosus .…”
Section: Discussionmentioning
confidence: 99%
“…A noninvasive evaluation of PAS can be implemented by an echocardiographic method which is firstly described for aorta in 1988 . PAS may increase as a result of many situations affecting right heart chambers . However, it has been still unknown whether elastic properties of pulmonary artery deteriorate in patients with OSAS.…”
mentioning
confidence: 99%
“…20 Although the relationship between them has not been fully explained, it was reported that the increase in PAS is an important factor contributing to RV afterload and eventual RV failure. [8][9][10][11][12][13][14] In this population, pulmonary diseases affecting the right heart, especially OSAS and COPD, may cause right heart dysfunction without PHT. [8][9][10][11][12][13][14] In this population, pulmonary diseases affecting the right heart, especially OSAS and COPD, may cause right heart dysfunction without PHT.…”
Section: Pas Is a Relatively New Doppler Echocardiographic Parametermentioning
confidence: 99%
“…[8][9][10][11][12][13][14] There is a limited number of studies on cardiovascular complications of asthma. In primary bronchopulmonary diseases, hypoxia-induced changes may cause PAS to increase by triggering remodeling in the pulmonary vascular structure.…”
mentioning
confidence: 99%
“…Tissue Doppler imaging was used to obtain the right ventricular myocardial velocities (S') in the apical four-chamber view with a sample volume placed at the lateral segment of the tricuspid annulus. The parameters necessary for calculation of MPI were obtained by tissue Doppler in the apical four-chamber view (11). Tricuspid annular plane systolic excursion (TAPSE) represents the distance of systolic excursion of the right ventricular annular plane towards the apex and is measured as the maximum apical excursion of the lateral tricuspid annular plane as previously described (7).…”
Section: Echocardiographic Measurementsmentioning
confidence: 99%